Marketing wines to South African Millennials : the effect of expert opinions on the perceived quality of Pinotage wines - Vannevel, Margaux (Stellenbosch : Stellenbosch University, 2016)
Thesis (MAgricAdmin)--Stellenbosch University, 2016.